Before the Ethical Policy: The Ottoman State, Pan-Islamism, and Modernisation in Indonesia, 1898â1901 - Supratman, Frial Ramadhan (Al-Jamiah: Journal of Islamic Studies, 2016)
By drawing on Ottoman-Turkish documents in the Prime Ministerâs Ottoman Archives, this paper investigates the role of the Ottoman state and Pan-Islamic ideology on modernisation in Indonesia. The article revisits the process defining the Ethical Policy (Politik Etis) as the turning point of the emergence of modernisation in Indonesia.Â  In existing scholarship, the âEthical Policyâ became the grand narrative in Indonesian history, meanwhile the influence of Pan-Islamism is only seen as the unsuccessful political propaganda of Abdulhamid II on the anti-colonialism movement in Indonesia. Many Indonesian and Ottoman historians view Pan-Islamism in the context of anti-colonialism fighting against the Dutch militarily in the late nineteenth and early twentieth centuries. This article proposes an alternative view to this narrative which acknowledges Pan-Islamism as a modernisation step for Indonesians which was signed by the Jawi students arrival in Istanbul and shows the Hadhrami community as the agent of modernisation. In short, the article shows the Ottoman influence on the emergence of the Ethical Policy of 1901 in Indonesia.[Menggunakan dokumen-dokumen Turki Utsmani yang disimpan di Prime Ministerâs Ottoman Archives, makalah ini meneliti peran imperium Utsmani dan ideologi Pan-IslamÂ  dalam modernisasi Indonesia. Hal itu dilakukan dengan meninjau kembali proses mendefinisikan Politik Etis sebagai titik balik lahirnya modernisasi Indonesia. Dalam literatur yang ada sekarang, Politik Etis menjadi cerita utama dalam sejarah Indonesia, sementara Pan-Islamisme hanya dipandang sebagai propaganda gagal dari Abdulhamid II bagi gerakan anti kolonial di Indonesia. Kebanyakan sejarawan di Indonesia dan Turki dalam konteks perjuangan melawan penjajah Belanda. Artikel ini menawarkan narasi alternatif yangÂ  mengakui Pan-Islamisme sebagai salah satu tahapan penting modernisasi Indonesia yang ditandai dengan datangnya para mahasiswa Jawa di Istambul dan menunjukkan peran komunitas Hadhrami sebagai agen modernisasi.]